Ensayo comparativo de nueve híbridos dobles de maíz (Zea mays L.) amarillo duro bajo condiciones de secano en el valle Bajo Mayo — San Martin - Ushiñahua Ramirez, Daniel (1994)
This thesis was carried out in the field of Agricultural Experimental Station "El Porvenir"; in the Valle del Bajo Mayo, San Martin province and region. (Peru), geographically characterized by having the following coordinates: West 76 ° 26 Length ', 06 ° 34' South Latitude and 356 meters above sea level, with the aim of determining one or more double hybrids superior in performance and adaptable to dry conditions in the area and make economic analysis of the best treatments features. performance and additional vegetative characteristics of double hybrids in upland tropical diseases was evaluated using statistical design Block Completely Randomized (BCR) with 10 treatments and 4 replications, which raised were analyzed using Analysis of Variance and Multiple Test Duncan . The experimental soil was residual origin flat and machined surface, with sandy clay loam, reaction slightly acidic (pH 6.6), media content organic matter (2.5 '), average total nitrogen (0.13%), phosphorus normal potassium . The planting distance was 0.80 m. between bumps and 0.80 m. between rows, wet ground. Composting was done using the dose of 90 kg. Nitrogen per hectare applied the 50% remaining 30 days following urea and receiving a total rainfall during the growing season of 595 mm, and T ° average of 26.04 * C. Oe the results obtained according to the statistical analysis concludes that there was statistical differences with treatments on grain yield to 14% moisture, due to the differences that have interacted with the ecological environment, whose yields fluctuated between 3.34 and 1.17 MT / it has to correspond to double hybrid T4 = (Bra.2 x RD4) (Gua.6 x Col. 3} and T9 = (Cua.6 x RD4) (Col. 3 x CB.1) the highest and lowest respectively, having surpassed statistically higher performance which reached the witness M - 28 - T. T4 = double hybrid (RD4 Bra.2 x) (x Col.3 Cua.6), T2 = (x Bra.2 RD4) (x CB.1 Gua.6) and T8 = (Col.3 X RD4) (Cua.6 x CB.1), they noted for their greater ability in performance, including existi6 no statistical difference; but only the T4 treatment exceeded the variety witness Marginal 28 Tropical (M - 28 - T) yield reached 2.14 MT / ha, reaching 8 "place in order of merit. According to the benefit / cost determined deficit values ​​for the three best treatments including witness.